Evaluasi efektivitas model kooperatif learning tipe jigsaw dalam pembelajaran matematika kelas X di SMA N 1 Prambanan tahun 2012/2013 - Rini Utami (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
The process designed and implemented as a systematic procedure that will lead to the achievement of learning objectives held. The purpose of this study to examine whether the type of learning with the learning model for learning mathematics Jigsaw can give a positive reaction, change behavior, improve learning outcomes and enhance morale impact student learning. The evaluation was done in SMA N 1 Prambanan school year 2012/2013. Evaluation of the student population is a class X. Sample evaluation is the first grade (x f) students totaling 30 students. This evaluation Kirkpatrick evaluation model consisting of four components, namely: 1) Evaluation of reaction (Reaction Evaluation), 2) Evaluation of Learning (Learning Evaluation),Â 3) Evaluation of Behavior (Behavior Evaluation), and 4) Evaluation Results (Result Evaluation. DataÂ were collected through questionnaires for student reactions, observations on the implementation of the learning process, observation of student behavior, ability test to value learning outcomes, and the results of the questionnaire for the impact. The technique of data analysis using quantitative descriptive. The results of the discussion of the evaluation that learning mathematics using Jigsaw type learning model as follows: (a) the reaction gave a positive reaction with 86.46, categorized as excellent, (b) the learning, can improve their learning / absorption in students with a mean of 78 with 83% of students to achieve mastery, (c) the behavior, may be increased activity of students with a 20.1 average in the category of very good, (d) the result as a result of the type of learning averages 79 Jigsaw achieve good category. Thus concluded that the type of evaluation Jigsaw learning model can improve the learning process with evidence of absorption of students has increased compared to the pre-test. This means that the type of Jigsaw learning model very effectively